Sameness, Ellipsis and Anaphor - Hardt, Daniel; Mikkelsen, Line; Ørsnes, Bjarne (Proceedings of the Amsterdam Colloquium, 2011)
We compare explicit assertions of sameness with analogous elliptical and anaphoric expressions, and find striking differences in their interpretation. We account for those differences with a two part proposal: first, we propose that same is additive, similar to too. Second, same must take scope over a containing event-denoting expression. We give evidence that the scope-taking of same is subject to standard island constraints, and we also show that same always compares two event-denoting clauses that differ in a relevant property.